Laminate, optical member, and optical device
The laminate structure with a hard adhesive layer and void layer balances refractive index and peel strength, achieving low refractive index and high mechanical strength through specific hardness and peel strength criteria.
Patent Information
- Application Number
- JP2023107488
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
There is a trade-off relationship between the refractive index and peel strength in laminates with void layers and adhesive layers, where softer adhesives increase peel strength but permeate into voids, raising refractive index, while harder adhesives maintain low refractive index but reduce peel strength.
A laminate structure is developed with a void layer and an adhesive layer, where the adhesive layer has a nanoindentation hardness of 0.5 MPa or more and an interlayer peel strength of 3 N/25 mm or more, ensuring a refractive index of 1.30 or less.
The laminate achieves a low refractive index and excellent mechanical strength by balancing the hardness of the adhesive layer with the void layer, maintaining porosity and peel strength.
Smart Images

Figure 2025006593000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a laminate, an optical member, and an optical device. [Background technology]
[0002] In optical devices, for example, it has been proposed to use a low refractive index layer as a total reflection layer. For example, Patent Document 1 discloses a laminate in which a layer having a lower refractive index than the light guide plate is inserted between the light guide plate and the reflector plate. As the low refractive index layer, for example, a gap layer having voids is used in order to make the refractive index as close as possible to that of air. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-62626 Summary of the Invention [Problem to be solved by the invention]
[0004] An optical member including a void layer is generally used in a laminated structure (laminate) in which the members are bonded together with a pressure-sensitive adhesive layer or a bonding layer (hereinafter, sometimes collectively referred to as a "tacky adhesive layer").
[0005] Here, in the case of a laminate in which the void layer and the adhesive layer are directly laminated, if the adhesive layer is soft, the peel strength between the layers in the laminate tends to be high. On the other hand, since the adhesive layer is soft, the adhesive layer penetrates into the voids of the void layer, resulting in a decrease in the porosity of the void layer and a tendency for the refractive index of the void layer contained in the laminate to be high. On the other hand, if the adhesive layer is hard, the adhesive layer does not easily penetrate into the voids of the void layer, so the refractive index of the void layer contained in the laminate can be maintained low, but the peel strength (mechanical strength) between the layers in the laminate tends to be low. Thus, in a laminate including a void layer and an adhesive layer, there is a trade-off between the refractive index of the void layer contained in the laminate and the peel strength between the layers in the laminate. Therefore, it is desired to realize a laminate having high mechanical strength even if it has a low refractive index.
[0006] In view of the above, an object of the present disclosure is to provide a laminate, an optical member, and an optical device that have a low refractive index and excellent mechanical strength. [Means for solving the problem]
[0007] In order to achieve the above object, the laminate of the present disclosure comprises: A porous layer and an adhesive layer, The adhesive layer is directly laminated on one or both sides of the porous layer, the refractive index of the air gap layer measured in the laminate state is 1.30 or less, The nanoindentation hardness measured by pressing an indenter into the adhesive layer by 2000 nm using a nanoindenter is 0.5 MPa or more; The interlaminar peel strength between the porous layer and the adhesive layer is 3 N / 25 mm or more, as measured using a tensile tester at a tensile speed of 0.3 m / min.
[0008] The optical member of the present disclosure includes the laminate of the present disclosure.
[0009] The optical device of the present disclosure includes the optical member of the present disclosure. Effect of the Invention
[0010] According to the present disclosure, it is possible to provide a laminate, an optical member, and an optical device that have a low refractive index and excellent mechanical strength. [Brief description of the drawings]
[0011] [Figure 1] 1(a) and (b) are cross-sectional views illustrating examples of the configuration of a laminate according to the present disclosure. [Diagram 2] 2(a) and (b) are cross-sectional views showing another example of the configuration of the laminate of the present disclosure. [Diagram 3] 3(a) and (b) are cross-sectional views showing still another example of the configuration of the laminate of the present disclosure. [Figure 4] FIG. 4 is a graph showing the relationship between peel strength and refractive index. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Next, the present disclosure will be described in more detail with reference to examples. However, the present disclosure is not limited to the following description.
[0013] In the present disclosure, the "adhesive layer" refers to a layer formed by at least one of an adhesive and an adhesive. In the present disclosure, unless otherwise specified, the "adhesive layer" may be an "adhesive layer" formed by an adhesive, an "adhesive layer" formed by an adhesive, or a layer containing both an adhesive and an adhesive. In the present disclosure, an adhesive and an adhesive may be collectively referred to as an "adhesive". In general, an agent having a relatively weak adhesive or bonding strength (e.g., an agent that allows the adherend to be peeled off again) may be called an "adhesive", and an agent having a relatively strong adhesive or bonding strength (e.g., an agent that does not allow the adherend to be peeled off again or is very difficult to peel off again) may be called an "adhesive". In the present disclosure, there is no clear distinction between an adhesive and an adhesive. In the present disclosure, there is no clear distinction between "adhesive strength" and "adhesive strength".
[0014] In the present disclosure, "on" or "on the surface" may refer to a state in which the material is in direct contact with the surface, or may refer to a state in which another layer or the like is interposed therebetween.
[0015] In the present disclosure, "interlayer" means any part between one layer and another layer, including the one layer and the other layer. That is, for example, when referring to the interlayer between one layer and another layer, it may be any part of the one layer, any part of the other layer, or any part of another layer between the one layer and the other layer. It may also be a boundary part between any two layers among the one layer, the other layer, and the other layer.
[0016] [1. Laminate] As described above, the laminate of the present disclosure includes a void layer and a tacky adhesive layer. The tacky adhesive layer is directly laminated on one or both sides of the void layer. In the present disclosure, the tacky adhesive layer is "directly laminated" on the void layer, for example, the tacky adhesive layer may be in direct contact with the void layer, or the tacky adhesive layer may be laminated on the void layer via the intermediate layer.
[0017] The cross-sectional view of FIG. 1(a) shows an example of the configuration of the laminate of the present disclosure. As shown in the figure, in this laminate 10, an adhesive layer 12 is directly laminated on one side of a void layer 11. Here, the nanoindentation hardness measured by pressing an indenter 2000 nm into the adhesive layer 12 using a nanoindenter (hereinafter, sometimes referred to as "nanoindentation hardness") is 0.5 MPa or more. In addition, the interlayer peel strength between the void layer 11 and the adhesive layer 12 measured at a tensile speed of 0.3 m / min using a tensile tester is 3 N / 25 mm or more. Furthermore, the refractive index of the void layer 11 measured as the laminate 10 is 1.30 or less.
[0018] 1(b) is a cross-sectional view showing another example of the configuration of the laminate of the present disclosure. As shown in the figure, this laminate 10a has adhesive layers 12 directly laminated on both sides of a porous layer 11.
[0019] In addition, as described above, the laminate of the present disclosure may have an intermediate layer between the void layer and the tacky adhesive layer, and the intermediate layer may be a layer formed by merging the void layer and the tacky adhesive layer. FIG. 2 shows an example of such a laminate of the present disclosure. As shown in the figure, the laminate 10b of FIG. 2(a) has a tacky adhesive layer 12 directly laminated on one side of the void layer 11. This laminate 10b is the same as the laminate 10 of FIG. 1(a) except that an intermediate layer 13 is present between the void layer 11 and the tacky adhesive layer 12. The intermediate layer 13 is a layer formed by merging the void layer 11 and the tacky adhesive layer 12. As shown in the figure, the laminate 10c of FIG. 2(b) has a tacky adhesive layer 12 directly laminated on both sides of the void layer 11. This laminate 10c is the same as the laminate 10a of FIG. 1(b) except that an intermediate layer 13 is present between the void layer 11 and each tacky adhesive layer 12. The intermediate layer 13 is a layer formed by combining the void layer 11 and the adhesive layer 12, as in FIG. 2(a).
[0020] The laminate of the present disclosure may or may not include other components other than the void layer, the tacky adhesive layer, and the intermediate layer. The other components are not particularly limited, and may be, for example, a substrate. The substrate is also not particularly limited, and may be, for example, a film (for example, a resin film), a glass plate, or the like, as described below. FIG. 3 shows an example of such a laminate of the present disclosure. The laminate 10d of FIG. 3(a) is the same as the laminate 10b of FIG. 2(a) except that, as shown in the figure, a substrate 14 is provided in direct contact with the surface of the void layer 11 opposite the tacky adhesive layer 12, and on the surface of the tacky adhesive layer 12 opposite the void layer 11. The laminate 10e of FIG. 3(b) is the same as the laminate 10c of FIG. 3(b) except that, as shown in the figure, a substrate 14 is provided in direct contact with the surface of the tacky adhesive layer 12 on both sides opposite the void layer 11. In FIG. 3(a) and FIG. 3(b), a substrate 14 is provided on both sides of the laminate. However, the present disclosure is not limited thereto, and for example, the substrate 14 may be provided on only one side. In addition, in FIG. 3(a) and FIG. 3(b), the substrate 14 is provided so as to be in direct contact with the void layer 11 or the tacky adhesive layer 12. However, the present disclosure is not limited thereto, and for example, other components may be present between the substrate 14 and the void layer 11 or the tacky adhesive layer 12. The other components are not particularly limited, and may be, for example, an optical functional layer. The optical functional layer is also not particularly limited, and may be, for example, an optical functional layer used in a general optical film, and may be, for example, a microlens film, a prism film, a diffusion film, a polarizing reflection film, a polarizing film, a retardation film, a high refractive index layer, etc.
[0021] The void layer is, for example, a void layer in which the pulverized gel silicon compound is chemically bonded. By using the pulverized gel silicon compound, the three-dimensional structure of the gel silicon compound is destroyed, and a new three-dimensional structure different from the gel silicon compound is formed. In this way, the void layer is a layer in which a new pore structure (new void structure) that cannot be obtained in a layer formed from the gel silicon compound is formed, and a nanoscale void layer with high porosity can be formed. In addition, when the void layer is, for example, a gel silicon compound, the pulverized materials are chemically bonded to each other while adjusting the number of siloxane bond functional groups of the gel silicon compound. Here, the "gel silicon compound" refers to a polymeric porous body containing siloxane bonds, and includes, for example, a porous body containing silsesquioxane as a constituent unit. In addition, after a new three-dimensional structure is formed as a precursor of the void layer, the void layer is chemically bonded (e.g., cross-linked) in a bonding step, so that the void layer has a structure having voids, for example, when the void layer is a functional porous body, but can maintain sufficient strength and flexibility. Therefore, according to the present disclosure, the void layer can be easily and simply applied to various objects.
[0022] In the void layer, the form in which the pulverized materials are chemically bonded (form of chemical bond) is not particularly limited, and specific examples of the chemical bond include, for example, covalent bonds, ionic bonds, and metal bonds. For example, the pulverized materials may be cross-linked (cross-linked) by covalent bonds. In addition, the form of chemical bond (for example, the above-mentioned cross-linking) of the pulverized materials may be, for example, a form in which the pulverized materials are directly bonded to each other, or a form in which the pulverized materials are indirectly bonded to each other via other substances such as cross-linking assistants, linkers, and spacers. The method of chemically bonding the pulverized materials is as described in the manufacturing method of the void layer described later.
[0023] The crosslinked bond is, for example, a siloxane bond. Examples of the siloxane bond include the following T2 bond, T3 bond, and T4 bond. When the gel silicon compound has a siloxane bond, it may have, for example, any one type of bond, any two types of bonds, or all three types of bonds. The higher the ratio of T2 and T3 among the siloxane bonds, the more flexible the gel is, and the gel's inherent properties can be expected, but the film strength becomes weak. On the other hand, if the ratio of T4 among the siloxane bonds is high, the film strength is easily expressed, but the void size becomes small and the flexibility becomes weak. For this reason, it is preferable to change the ratio of T2, T3, and T4 depending on the application, for example.
[0024] [ka]
[0025] When the void layer has the siloxane bond, the ratio of T2, T3 and T4, for example, when expressed relatively with T2 being "1", is T2:T3:T4=1:[1-100]:[0-50], 1:[1-80]:[1-40], 1:[5-60]:[1-30].
[0026] In the void layer, the gel silicon compound is, for example, a compound in which a silane compound is condensed or partially condensed. The condensation can be, for example, dehydration condensation. The partially condensed state refers to, for example, a state in which some of the condensable functional groups (e.g., alkoxy groups, etc.) contained in the silane compound are condensed, and the other functional groups are not condensed and the condensable functional groups remain. In other words, for example, some of the silane compounds are siloxane-bonded, and the other silane compounds are unbonded. The proportion of the unbonded silane compounds is, for example, less than 50%, 30% or less, or 15% or less.
[0027] The silane compound may include, for example, a monofunctional to trifunctional silane compound and a tetrafunctional silane compound. The silane compound may include, for example, at least one silane compound selected from monofunctional to trifunctional silane compounds, and may further include a tetrafunctional silane compound. The monofunctional to trifunctional silane compound may include, for example, a monofunctional to trifunctional alkoxysilane. The tetrafunctional silane compound may include, for example, a tetrafunctional alkoxysilane. The monofunctional silane compound may include, for example, trimethylmethoxysilane (TMMS), trimethylethoxysilane (TMES), trimethylpropoxysilane (TMPS), and the like. The bifunctional silane compound may include, for example, dimethyldimethoxysilane (DDMS), dimethyldiethoxysilane (DDES), dimethyldipropoxysilane (DDPS), and the like. Examples of the trifunctional silane compound include methyltrimethoxysilane (MTMS), methyltriethoxysilane (MTES), methyltrippropoxysilane (MTPS), 3-acryloxypropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, 4-vinylbutyltrimethoxysilane, 4-vinylbutyltriethoxysilane, 8-vinyloctyltrimethoxysilane, 8-vinyloctyltriethoxysilane, 10-methacryloyloxydecyltrimethoxysilane, 10-acryloyloxydecyltrimethoxysilane, 10-methacryloyloxydecyltriethoxysilane, 10-acryloyloxydecyltriethoxysilane, etc. Examples of the tetrafunctional silane compound include tetramethoxysilane (TMOS), tetraethoxysilane (TEOS), tetrapropoxysilane (TPOS), etc.
[0028] The content ratio of the tetrafunctional silane compound relative to the amount of the mono- to trifunctional silane compound is, for example, 1 to 25 mol%. The lower limit of the content ratio is, for example, 2 mol% or more, 3 mol% or more, or 3.5 mol% or more, and the upper limit is, for example, 20 mol% or less, 15 mol% or less, or 10 mol% or less, and the range is, for example, 2 to 20 mol%, 3 to 15 mol%, 3.5 to 15 mol%, or 3.5 to 10 mol%. It is preferable that the content ratio is not too high, for example, from the viewpoint of ease of pulverization in the gel pulverization step. It is also preferable that the content ratio is not too low, for example, from the viewpoint of improving the strength of the low refractive index layer.
[0029] The void layer is, for example, a void layer in which the pulverized gel silicon compound is chemically bonded in the presence of an additive. The additive may contain, for example, at least one of a crosslinking reaction accelerator and a precursor thereof. The crosslinking reaction accelerator may be, for example, an acidic substance or a basic substance. The crosslinking reaction accelerator may be, for example, a catalyst that promotes chemical bonding (crosslinking) between the pulverized gel silicon compound. The precursor of the crosslinking reaction accelerator may be, for example, a substance (crosslinking accelerator generator) that generates the crosslinking reaction accelerator by light or heat.
[0030] As a chemical reaction for chemically bonding the gel silicon compounds together, it is preferable to utilize a dehydration condensation reaction of the residual silanol groups contained in the silica sol molecules. By promoting the reaction between the hydroxyl groups of the silanol groups with the crosslinking reaction promoter, continuous film formation is possible in which the void structure is hardened in a short time. Examples of the crosslinking reaction promoter include a photoactive catalyst and a thermally active catalyst. With the photoactive catalyst, for example, in the bonding step described below, the gel silicon compounds can be chemically bonded (for example, crosslinked) together without heating. With this, for example, in the bonding step, the crushed material to be bonded is unlikely to shrink, so that a higher void ratio can be maintained. For example, in addition to or instead of the photoactive catalyst, a substance that generates a catalyst by light (photocatalyst generator) may be used, and in addition to or instead of the thermally active catalyst, a substance that generates a catalyst by heat (thermal catalyst generator) may be used. The photocatalyst generator is not particularly limited, but examples thereof include a photobase generator (a substance that generates a basic catalyst when irradiated with light) and a photoacid generator (a substance that generates an acidic catalyst when irradiated with light), and a photobase generator is preferred.Examples of the photobase generator include 9-anthrylmethyl N,N-diethylcarbamate (trade name WPBG-018), (E)-1-[3-(2-hydroxyphenyl)-2-propenoyl]piperidine (trade name WPBG-027), 1-(anthraquinon-2-yl)ethyl imidazolecarboxylate (trade name WPBG-140), 2-nitrophenylmethyl 4-methacryloyloxypiperidine-1-carboxylate (trade name WPBG-165), and 1,2-diisopropyl-3-[bis(dimethylamino)methylene]guanidium. Examples of the photoacid generator include 2-(3-benzoylphenyl)propionate (trade name WPBG-266), 1,2-dicyclohexyl-4,4,5,5-tetramethylbiguanidium n-butyltriphenylborate (trade name WPBG-300), and 2-(9-oxoxanthen-2-yl)propionic acid 1,5,7-triazabicyclo[4.4.0]dec-5-ene (Tokyo Chemical Industry Co., Ltd.), and a compound containing 4-piperidinemethanol (trade name HDPD-PB100: manufactured by Heraeus). Note that the trade names containing "WPBG" are all trade names of Wako Pure Chemical Industries, Ltd. Examples of the photoacid generator include aromatic sulfonium salts (trade name SP-170: manufactured by ADEKA), triarylsulfonium salts (trade name CPI101A: manufactured by San-Apro), and aromatic iodonium salts (trade name Irgacure250: manufactured by Ciba Japan). In addition, the crosslinking reaction accelerator that chemically bonds the pulverized gel silicon compound is not limited to the photoactive catalyst and the photocatalyst generator, and may be, for example, a thermally active catalyst or a thermal catalyst generator such as urea.The crosslinking reaction accelerator that chemically bonds the pulverized gel silicon compound may be, for example, a base catalyst such as potassium hydroxide, sodium hydroxide, or ammonium hydroxide, or an acid catalyst such as hydrochloric acid, acetic acid, or oxalic acid.Among these, a base catalyst is preferred.The crosslinking reaction accelerator and its precursor can be used by adding at least one of the crosslinking reaction accelerator and its precursor to a sol particle liquid (e.g., a suspension) containing the pulverized material (gel-like silicon compound) immediately before coating, or as a mixed liquid in which at least one of the crosslinking reaction accelerator and its precursor is mixed in a solvent. The mixed liquid may be, for example, a coating liquid directly added to the sol particle liquid and dissolved, a solution in which at least one of the crosslinking reaction accelerator and its precursor is dissolved in a solvent, or a dispersion in which at least one of the crosslinking reaction accelerator and its precursor is dispersed in a solvent. The solvent is not particularly limited, and examples thereof include water and buffer solutions. The amount of the crosslinking reaction accelerator and its precursor added is not particularly limited, and is, for example, 0.01 to 20% by weight, 0.05 to 10% by weight, or 0.1 to 5% by weight, based on the weight of the gel-like silicon compound.
[0031] The lower limit of the total content ratio of the crosslinking reaction accelerator and its precursor relative to the total substance amount of the mono- to trifunctional silane compound and the tetrafunctional silane compound is, for example, 1 mol% or more, 1.5 mol% or more, 2 mol% or more, or 2.5 mol% or more, and the upper limit is, for example, 5 mol% or less, 4 mol% or less, 3.5 mol% or less, or 3 mol% or less.
[0032] In addition, when the silane compound in the gap layer does not contain the tetrafunctional silane compound, the lower limit of the total content of the crosslinking reaction accelerator and its precursor relative to the total amount of substance of the silane compounds is, for example, 1.5 mol% or more, 2 mol% or more, or 2.5 mol% or more, and the upper limit is, for example, 5 mol% or less, 4 mol% or less, 3.5 mol% or less, or 3 mol% or less.
[0033] In addition, the additive may include, for example, a crosslinking auxiliary. The crosslinking auxiliary can be, for example, a medium for indirectly bonding the pulverized gel silicon compound to each other by chemical bonding between the pulverized gel silicon compound and the crosslinking auxiliary. The crosslinking auxiliary enters between the pulverized gel silicon compound, and the pulverized gel silicon compound and the crosslinking auxiliary interact or bond with each other, so that the pulverized gel silicon compound that is somewhat distant from each other can be bonded to each other, and the strength can be efficiently increased.
[0034] The crosslinking auxiliary is preferably a multi-crosslinking silane monomer. Specifically, the multi-crosslinking silane monomer may have, for example, 2 to 3 alkoxysilyl groups, the chain length between the alkoxysilyl groups may be 1 to 10 carbon atoms, and may contain elements other than carbon. Examples of the crosslinking auxiliary include bis(trimethoxysilyl)ethane, bis(triethoxysilyl)ethane, bis(trimethoxysilyl)methane, bis(triethoxysilyl)methane, bis(triethoxysilyl)propane, bis(trimethoxysilyl)propane, bis(triethoxysilyl)butane, bis(trimethoxysilyl)butane, bis(triethoxysilyl)pentane, bis(trimethoxysilyl)pentane, bis(triethoxysilyl)hexane, bis(trimethoxysilyl)hexane, bis(trimethoxysilyl)-N-butyl-N-propyl-ethane-1,2-diamine, tris-(3-trimethoxysilylpropyl)isocyanurate, and tris-(3-triethoxysilylpropyl)isocyanurate. The amount of the crosslinking auxiliary added is not particularly limited, but is, for example, 0.01 to 20% by weight, 0.05 to 15% by weight, or 0.1 to 10% by weight relative to the weight of the gel silicon compound.
[0035] The lower limit of the total content of the crosslinking auxiliary relative to the total amount of the mono- to trifunctional silane compound and the tetrafunctional silane compound is, for example, 1 mol% or more, 2 mol% or more, 2.5 mol% or more, or 3 mol% or more, and the upper limit is, for example, 6 mol% or less, 5.5 mol% or less, 5 mol% or less, 4.5 mol% or less, or 3.5 mol% or less.
[0036] In addition, when the silane compound in the gap layer does not include the tetrafunctional silane compound, the lower limit of the total content of the crosslinking auxiliary relative to the total amount of substance of the silane compounds is, for example, 2 mol% or more, or 2.5 mol% or more, and the upper limit is, for example, 6 mol% or less, 5 mol% or less, 4 mol% or less, 3.5 mol% or less, or 3 mol% or less.
[0037] The void layer has, for example, a pore structure. The void size of the pores in the void layer refers to the diameter of the long axis of the void (hole) among the diameter of the long axis and the diameter of the short axis. The pore size is, for example, 5 nm to 200 nm. The void size is, for example, 5 nm or more, 10 nm or more, or 20 nm or more, and the upper limit is, for example, 200 nm or less, 150 nm or less, 100 nm or less, 50 nm or less, 40 nm or less, or 30 nm or less, and the range is, for example, 5 nm to 200 nm, or 10 nm to 100 nm. The void size is determined according to the application of the void structure, so it is necessary to adjust it to a desired void size according to the purpose, for example. The void size can be evaluated, for example, by the following method.
[0038] (Cross-sectional SEM observation of void layer) In the present disclosure, the morphology of the void layer can be observed and analyzed using a SEM (scanning electron microscope). Specifically, for example, the void layer is subjected to FIB processing (accelerating voltage: 30 kV) under cooling, and a cross-sectional electron image can be obtained at a magnification of 100,000 times using a FIB-SEM (manufactured by FEI: product name Helios NanoLab600, accelerating voltage: 1 kV) for the obtained cross-sectional sample.
[0039] (Evaluation of void size) In the present disclosure, the pore size can be quantified by the BET test method. Specifically, 0.1 g of a sample (the pore layer) is placed in the capillary of a pore distribution / specific surface area measuring device (BELLSORP MINI / product name of Microtrack Bell Co., Ltd.), and then the sample is dried under reduced pressure at room temperature for 24 hours to remove the gas from the pore structure. Then, nitrogen gas is adsorbed onto the sample, and a BET plot, a BJH plot, and an adsorption isotherm are plotted to determine the pore distribution. This allows the pore size to be evaluated.
[0040] The void layer may have a pore structure (porous structure) as described above, and may be an open-cell structure in which the pore structure is continuous. The open-cell structure means, for example, that the pore structure is three-dimensionally connected in the void layer, and may be a state in which the internal voids of the pore structure are continuous. When the porous body has an open-cell structure, it is possible to increase the porosity in the bulk, but when closed-cell particles such as hollow silica are used, an open-cell structure cannot be formed. In contrast, the void layer has a three-dimensional dendritic structure of sol particles (crushed porous gel forming a sol), and therefore the dendritic particles settle and deposit in the coating film (coated film of sol containing the crushed porous gel), making it easy to form an open-cell structure. In addition, it is more preferable that the void layer forms a monolith structure in which the open-cell structure has a plurality of pore distributions. The monolith structure refers to, for example, a structure in which nano-sized fine voids exist and a hierarchical structure in which the nano-voids are aggregated and exist as an open-cell structure. When forming the monolithic structure, for example, it is possible to achieve both membrane strength and high porosity by imparting membrane strength with fine pores and high porosity with coarse open-cell pores. To form such a monolithic structure, for example, it is important to first control the pore distribution of the pore structure to be generated in the porous gel prior to pulverization into the pulverized material. In addition, for example, when pulverizing the porous gel, the particle size distribution of the pulverized material can be controlled to a desired size to form the monolithic structure.
[0041] In the air gap layer, the haze indicating transparency is not particularly limited, and the lower limit is, for example, 0.1% or more, 0.2% or more, or 0.3% or more, and the upper limit is, for example, 10% or less, 5% or less, or 3% or less, and the range is, for example, 0.1 to 10%, 0.2 to 5%, or 0.3 to 3%.
[0042] The haze can be measured, for example, by the following method.
[0043] (Hayes's rating) The void layer (the void layer) is cut to a size of 50 mm x 50 mm, and is set in a haze meter (Murakami Color Research Laboratory: HM-150) to measure the haze. The haze value is calculated according to the following formula. Haze (%) = [Diffuse transmittance (%) / Total light transmittance (%)] x 100 (%)
[0044] The refractive index of a medium is generally defined as the ratio between the transmission speed of the wavefront of light in a vacuum and the propagation speed in the medium. In this disclosure, the refractive index is defined as the refractive index measured at a wavelength of 550 nm unless otherwise specified. The method for measuring the refractive index is not particularly limited, and can be measured, for example, by the following method.
[0045] The refractive index of the void layer when only the void layer is measured is, for example, 1.30 or less. The upper limit of the refractive index of the void layer when only the void layer is measured is, for example, 1.30 or less, less than 1.30, 1.26 or less, 1.25 or less, less than 1.25, 1.24 or less, 1.23 or less, or 1.22 or less, and the lower limit is, for example, 1.05 or more, 1.10 or more, 1.15 or more, 1.16 or more, 1.17 or more, 1.18 or more, or 1.19 or more, and the range is, for example, 1.05 or more and 1.30 or less, 1.05 or more and 1.30 or less, 1.10 or more and 1.25 or less, 1.15 or more and 1.25 or less, or 1.19 or more and 1.25 or less. The method for measuring the refractive index of the void layer when only the void layer is measured is not particularly limited, and can be measured, for example, by the following method.
[0046] The porosity of the porous layer has a lower limit of, for example, 30 volume% or more, or 50 volume% or more, and an upper limit of, for example, 90 volume% or less, 75 volume% or less, or 60 volume% or less, and the range is, for example, 30 to 90 volume%, 50 to 75 volume%, or 50 to 60 volume%.
[0047] (Evaluation of the refractive index of the gap layer when only the gap layer is measured) After forming a void layer (void layer in the laminate of the present disclosure) on an acrylic film, cut it to a size of 50 mm x 50 mm and attach it to the surface of a glass plate (thickness: 3 mm) with an adhesive layer. The center of the back surface of the glass plate (diameter: about 20 mm) is painted with black ink to prepare a sample that does not reflect on the back surface of the glass plate. The sample is set in an ellipsometer (JA Woollam Japan: VASE) and the refractive index is measured under conditions of a wavelength of 550 nm and an incident angle of 50 to 80 degrees, and the average value is taken as the refractive index.
[0048] The void remaining rate of the porous layer after a heat and humidity durability test in which the layer is maintained at a temperature of 85° C. and a humidity of 85% RH for 500 hours is, for example, at least 10 volume %, at least 20 volume %, at least 30 volume %, at least 40 volume %, at least 50 volume %, at least 60 volume %, at least 70 volume %, at least 80 volume %, at least 85 volume %, or greater than 85 volume %. When only the porous layer is measured, the method for measuring the refractive index of the porous layer is not particularly limited, and can be measured, for example, by the following method.
[0049] (Evaluation of void remaining rate in void layer) The laminate thus produced is placed in an oven at a temperature of 85° C. and a humidity of 85% RH, and a heat and humidity durability test is carried out for 500 hours. The degree to which the voids in the porous layer are filled after the heat and humidity durability test is confirmed by SEM, and the remaining porosity can be calculated.
[0050] The thickness of the void layer is not particularly limited, and the lower limit is, for example, 0.05 μm or more, or 0.1 μm or more, and the upper limit is, for example, 1000 μm or less, 100 μm or less, 10 μm or less, 5 μm or less, or 2 μm or less, and the range is, for example, 0.05 to 1000 μm, or 0.1 to 100 μm.
[0051] The form of the porous layer is not particularly limited, and may be, for example, a film shape or a block shape.
[0052] The method for producing the void layer is not particularly limited, but for example, the void layer can be produced by the method for producing the void layer described later or the method described in WO 2019 / 065999 and WO 2019 / 065803. The description of the publication is incorporated herein by reference.
[0053] In the present disclosure, the adhesive layer is not particularly limited. In the present disclosure, the adhesive or the adhesive forming the adhesive layer is not particularly limited, and for example, a general adhesive or adhesive can be used. Examples of the adhesive or the adhesive include polymer adhesives such as acrylic, vinyl alcohol, silicone, polyester, polyurethane, polyether, and rubber adhesives. In addition, examples include adhesives composed of water-soluble crosslinking agents of vinyl alcohol polymers such as glutaraldehyde, melamine, and oxalic acid. These adhesives and adhesives may be used alone or in combination (for example, mixed, laminated, etc.). The thickness of the adhesive layer is not particularly limited, and is, for example, 0.1 to 100 μm, 5 to 50 μm, 10 to 30 μm, or 12 to 25 μm.
[0054] In the adhesive layer of the laminate of the present disclosure, the nanoindentation hardness is 0.5 MPa or more as described above. The lower limit of the nanoindentation hardness may be, for example, 0.55 MPa or more, 0.6 MPa or more, or 0.65 MPa or more, and the upper limit may be, for example, 2.0 MPa or less, 1.5 MPa or less, 1.3 MPa or less, or 1.1 MPa or less. The method for measuring the nanoindentation hardness is not particularly limited, and can be measured, for example, by the following method.
[0055] (Nanoindentation hardness evaluation) A measurement sample is cut into a size of about 1 cm square and fixed to a predetermined support, and the nanoindentation hardness of the adhesive layer in the laminate of the present disclosure is measured under the following conditions. The nanoindentation hardness can be measured by a nanoindentation method. ·Analyzer: Hysitron Inc., Triboindenter ·Indenter used: Conical (spherical: diameter 20μm) Measurement method: Single indentation measurement ·Measurement temperature: room temperature Indentation depth: 2000nm
[0056] The nanoindentation hardness is calculated from the maximum load (Pmax) and contact projected area (A) obtained by the measurement using the following formula. Nanoindentation hardness = Pmax / A
[0057] The nanoindentation hardness may be the nanoindentation hardness of either the surface of the adhesive layer or the cross section of the adhesive layer.
[0058] In the laminate of the present disclosure, the peel strength between the void layer and the tacky adhesive layer measured at a tensile speed of 0.3 m / min using a tensile tester is 3 N / 25 mm or more as described above. The lower limit of the peel strength may be, for example, 3.5 N / 25 mm or more, 4.0 N / 25 mm or more, or 5.0 N / 25 mm or more. Since the mechanical strength between the layers of the laminate of the present disclosure is improved as the peel strength is higher, the upper limit of the peel strength is not particularly limited, but is, for example, 20 N / 25 mm or less, 15 N / 25 mm or less, or 10 N / 25 mm or less. The peel strength is, for example, a peel strength measured due to cohesive failure of the void layer. The method for measuring the peel strength is not particularly limited, and can be measured, for example, by the following method.
[0059] (Evaluation of interlayer peel strength) A resin film substrate having a void layer (void layer in the laminate of the present disclosure) and a tacky adhesive layer (tacky adhesive layer in the laminate of the present disclosure) formed thereon is prepared, and an acrylic adhesive layer (thickness 20 μm) is bonded to the opposite side of the void layer in the resin film substrate. The bonded sample is cut to 50 mm x 25 mm to prepare an adhesive tape piece. Next, the tacky adhesive layer (thickness 10 μm) on the void layer side is bonded to a PET film (T100: manufactured by Mitsubishi Plastics Film Co., Ltd.) cut into a strip of 25 mm x 100 mm, and the acrylic adhesive layer on the resin film substrate side is laminated with glass to fix it. The sample thus prepared is chucked in a tensile tester (manufactured by Shimadzu Corporation, product name: Autograph (registered trademark) AG-Xplus) so that the chuck distance is 100 mm, and then a 180° peel test is performed at a tensile speed of 0.3 m / min. A 50 mm peel test is carried out N=3 times, and the average test force is regarded as the peel strength between the layers.
[0060] The refractive index of the void layer measured in the laminate state is 1.30 or less, as described above. The upper limit of the refractive index of the void layer measured in the laminate state is, for example, 1.30 or less, less than 1.30, 1.26 or less, 1.25 or less, less than 1.25, 1.24 or less, 1.23 or less, or 1.22 or less, and the lower limit is, for example, 1.05 or more, 1.10 or more, 1.15 or more, 1.16 or more, 1.17 or more, 1.18 or more, or 1.19 or more, and the range is, for example, 1.05 or more and 1.30 or less, 1.05 or more and 1.30 or less, 1.10 or more and 1.25 or less, 1.15 or more and 1.25 or less, or 1.19 or more and 1.25 or less. The method for measuring the refractive index of the void layer measured in the laminate state is not particularly limited, and can be measured, for example, by the following method.
[0061] (Evaluation of the refractive index of the gap layer measured in the laminate state) A prism of a prism coupler (manufactured by Metricon) is attached to the substrate side of a laminate (glass / adhesive layer / gap layer / acrylic substrate) in which an adhesive layer is provided on a gap layer, and the total reflection critical angle is measured using a laser. The refractive index can be calculated from the measured critical angle.
[0062] The laminate of the present disclosure may satisfy the following condition (1), for example, when the refractive index is X and the peel strength is Y. Fig. 4 shows a graph illustrating the relationship between the peel strength and the refractive index under condition (1). In Fig. 4, the horizontal axis represents the refractive index, and the vertical axis represents the peel strength (N / 25 mm). Condition (1): Y≧80X-93.8
[0063] Furthermore, the laminate of the present disclosure may satisfy the following condition (2), for example, when the refractive index is X and the peel strength is Y. Fig. 4 shows a graph illustrating the relationship between the peel strength and the refractive index under condition (2). Condition (2): Y≧100X-117
[0064] When the condition (1) or the condition (2) is satisfied, for example, a laminate having a low refractive index and high peel strength (i.e., excellent mechanical strength) can be obtained. In order to satisfy the condition (1) and the condition (2), the types and content ratios of the tetrafunctional silane compound and the additives may be appropriately adjusted, for example, without being particularly limited.
[0065] In the present disclosure, the intermediate layer is not particularly limited, but for example, as described above, is a layer formed by integrating a part of the void layer with a part of the adhesive layer. The thickness of the intermediate layer is not particularly limited, but for example, is 1 to 1500 nm, 5 to 1000 nm, 10 to 800 nm, or 20 to 500 nm.
[0066] The form of the laminate of the present disclosure is not particularly limited, but is usually in the form of a film.
[0067] The laminate of the present disclosure is, for example, a roll body. The laminate of the present disclosure may further include a resin film, and the void layer may be formed on the long resin film, as described above. In this case, another long film may be laminated on the laminate of the present disclosure, and another long resin film (for example, an insert paper, a release film, a surface protection film, etc.) may be laminated on the laminate of the present disclosure including the resin film and the void layer, and then wound into a roll body.
[0068] The method for producing the laminate of the present disclosure is not particularly limited, and for example, the laminate can be produced by the production method of the present disclosure shown below. In addition, the method for producing the optical laminate of the present disclosure that does not include a resin film can be performed in the same manner as the production method of the laminate of the present disclosure, except that no resin film is used, unless otherwise specified.
[0069] [2. Manufacturing method of laminate] The method for producing the laminate of the present disclosure is not particularly limited, and may be, for example, the production method described below. However, the following description is merely an example and does not limit the present disclosure in any way.
[0070] As described above, the method for producing a laminate according to the present disclosure includes a void layer forming step of forming the void layer, and a tacky adhesive layer forming step of forming the tacky adhesive layer on the void layer. The method for producing a laminate according to the present disclosure may further include an intermediate layer forming step of reacting the void layer with the tacky adhesive layer to form the intermediate layer.
[0071] The void layer forming step (the method for manufacturing the void layer) may further include a gel silica synthesis step, a gel crushing step, and a bonding step. The void layer forming step (the method for manufacturing the void layer of the present disclosure) may or may not include other steps than the gel silica synthesis step, the gel crushing step, and the bonding step. The other steps are not particularly limited, and examples thereof include a coating step and a drying step, which will be described later.
[0072] The gel silica synthesis step includes, for example, a step of synthesizing a gel silicon compound by condensing or partially condensing the silane compound. The gel silica synthesis step may include, for example, a step of gelling a block of porous body in a solvent to form a gel. In this case, for example, the gel gelled by the gel silica synthesis step is used in the first grinding stage (for example, the first grinding stage) of the multiple grinding stages described below.
[0073] The method for producing the void layer includes, for example, an aging step of aging the gel in a solvent. In this case, for example, the gel after the aging step is used in the first crushing step (for example, the first crushing step) of the multiple crushing steps.
[0074] The gel crushing step includes, for example, a step of crushing the gel silicon compound to obtain a crushed product. The gel crushing step may be a single step, but is preferably divided into a plurality of crushing steps. The number of crushing steps is not particularly limited, and may be, for example, two steps, or three or more steps.
[0075] The volume average particle diameter of the gel after the first pulverization step may be, for example, 0.5 to 100 μm, 1 to 100 μm, 1 to 50 μm, 2 to 20 μm, or 3 to 10 μm. The volume average particle diameter of the gel after the second pulverization step may be, for example, 10 to 1000 nm, 100 to 500 nm, or 200 to 300 nm. The volume average particle diameter indicates the particle size variation of the pulverized material in the liquid containing the gel (gel-containing liquid). The volume average particle diameter can be measured, for example, by a particle size distribution evaluation device such as a dynamic light scattering method or a laser diffraction method, and an electron microscope such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0076] In the method for producing the void layer, for example, after the gel silica synthesis step, the solvent replacement step is performed to replace the solvent with another solvent. In this case, for example, the gel in the other solvent is used in the first crushing step (for example, the first crushing step) of the multiple crushing steps.
[0077] In at least one of the multiple grinding stages (e.g., at least one of the first grinding stage and the second grinding stage) of the method for manufacturing the porous layer, the grinding of the porous body is controlled, for example, while measuring the shear viscosity of the liquid.
[0078] At least one of the multiple pulverization steps (for example, at least one of the first pulverization step and the second pulverization step) in the method for producing the porous layer is carried out by, for example, high-pressure media-less pulverization.
[0079] In the following, in the method for producing the void layer, the gel powder-containing liquid obtained by a process including the gel crushing process may be simply referred to as "gel powder-containing liquid".
[0080] According to the gel pulverized material-containing liquid, for example, a coating film is formed, and the pulverized material in the coating film is chemically bonded in a bonding process to form the void layer as a functional porous body. According to the gel pulverized material-containing liquid, for example, the void layer can be applied to various objects. Therefore, the gel pulverized material-containing liquid and its manufacturing method are useful, for example, in manufacturing the void layer.
[0081] The gel powder-containing liquid has, for example, extremely excellent uniformity, and therefore, when the porous layer is used for applications such as optical components, the appearance of the optical components can be improved.
[0082] The gel powder-containing liquid may be, for example, a gel powder-containing liquid that is applied (coated) onto a substrate (coating process) and then dried (drying process) to obtain a layer having a high porosity (porous layer).
[0083] In the coating step, the coating method of the gel pulverized material-containing liquid is not particularly limited, and a general coating method can be adopted. Examples of the coating method include a slot die method, a reverse gravure coating method, a microgravure method (microgravure coating method), a dip method (dip coating method), a spin coating method, a brush coating method, a roll coating method, a flexographic printing method, a wire bar coating method, a spray coating method, an extrusion coating method, a curtain coating method, and a reverse coating method. Among these, from the viewpoint of productivity, smoothness of the coating film, and the like, an extrusion coating method, a curtain coating method, a roll coating method, a microgravure coating method, and the like are preferred. The coating amount of the gel pulverized material-containing liquid is not particularly limited, and can be appropriately set, for example, so that the thickness of the void layer is appropriate. The thickness of the void layer is not particularly limited, and is, for example, as described above.
[0084] In the drying step, the gel pulverized liquid is dried (i.e., the dispersion medium contained in the gel pulverized liquid is removed) to form the coating film (precursor of the void layer) after drying. The drying temperature in the drying step is, for example, 50 to 250°C, 60 to 150°C, or 70 to 130°C, and the drying time is, for example, 0.1 to 30 minutes, 0.2 to 10 minutes, or 0.3 to 3 minutes. The drying temperature and time are preferably lower and shorter in terms of, for example, continuous productivity and the development of a high porosity. If the conditions are too strict, for example, in the case of a resin film, the substrate may expand in a drying oven as the substrate approaches the glass transition temperature of the substrate, and defects such as cracks may occur in the formed void structure immediately after coating. On the other hand, if the conditions are too lenient, for example, in roll-to-roll processing, residual solvent is contained at the time of leaving the drying oven, and when rubbed against a roll in the next process, defects in appearance such as scratches may occur.
[0085] The drying method may be, for example, natural drying, heat drying, or reduced pressure drying. The drying method is not particularly limited, and for example, a general heating means can be used. Examples of the heating means include a hot air blower, a heating roll, and a far-infrared heater. Among them, when it is assumed that the product will be produced continuously on an industrial scale, it is preferable to use heat drying.
[0086] The bonding step includes a step of chemically bonding the pulverized material. The bonding step can be performed, for example, by irradiating or heating the coating film containing a catalyst or catalyst generator previously added to the gel pulverized material-containing liquid, or by spraying the catalyst onto the coating film and then irradiating or heating the coating film, or by irradiating or heating the coating film while spraying the catalyst or catalyst generator. The catalyst may be, for example, the crosslinking reaction accelerator, or a strength enhancer that enhances the strength of the void layer, and the crosslinking accelerator may also serve as the hardness enhancer.
[0087] The integrated light amount of the light irradiation is not particularly limited, but is, for example, 200 to 800 mJ / cm2 in terms of @360 nm. 2 , 250~600mJ / cm 2 , or 300 to 400 mJ / cm 2 From the viewpoint of preventing insufficient effect due to insufficient irradiation amount resulting in insufficient decomposition of the catalyst generator by light absorption, it is set to 200 mJ / cm 2 In order to prevent damage to the substrate under the air gap layer and the occurrence of thermal wrinkles, an integrated light quantity of 800 mJ / cm is recommended. 2 The following cumulative light quantities are recommended:
[0088] The heating temperature and heating time in the heating are not particularly limited, and the conditions of the heat treatment are not particularly limited. The heating temperature is, for example, 50 to 250°C, 60 to 150°C, or 70 to 130°C, and the heating time is, for example, 0.1 to 30 minutes, 0.2 to 10 minutes, or 0.3 to 3 minutes. Alternatively, the step of drying the applied gel pulverized material-containing liquid as described above may also serve as a step of carrying out a chemical reaction in the presence of the catalyst. That is, in the step of drying the applied gel pulverized material-containing liquid (e.g., suspension), the pulverized materials may be chemically bonded to each other by a chemical reaction in the presence of the catalyst. In this case, the pulverized materials (microporous particles) may be further bonded to each other by further heating the coating film after the drying step. Furthermore, it is presumed that the chemical reaction in the presence of the catalyst may also occur in the step of preparing the microporous particle-containing liquid (e.g., suspension) and the step of applying the microporous particle-containing liquid. However, this assumption does not limit the present invention in any way.
[0089] The adhesive layer forming step may include, for example, an adhesive coating liquid applying step of applying the adhesive coating liquid to a substrate, and a heat drying step of heating and drying the substrate coated with the adhesive coating liquid. For example, the adhesive layer side of an adhesive tape or the like having the adhesive layer laminated on a substrate may be attached to the void layer to form the adhesive layer on the void layer. In this case, the substrate such as the adhesive tape may be left attached as it is, or may be peeled off from the adhesive layer. In particular, by peeling off the substrate to form a laminate having no substrate (substrate-less), the thickness can be significantly reduced, and an increase in the thickness of a device or the like can be suppressed. In the present disclosure, the adhesive layer can be manufactured, for example, by using the adhesive coating liquid as described above.
[0090] The adhesive layer forming step can be carried out, for example, as follows. First, the adhesive coating liquid is produced by a mixing step of mixing all the components of the adhesive coating liquid. The adhesive coating liquid may contain, for example, a (meth)acrylic polymer, and may or may not further contain a crosslinking agent (for example, an isocyanate-based crosslinking agent or an epoxy-based crosslinking agent). The adhesive coating liquid may contain, for example, the (meth)acrylic polymer, a monomer having one or two reactive double bonds in one molecule, a crosslinking agent, and an organic peroxide. At this time, when the adhesive coating liquid contains other components, the other components may also be mixed together. For example, the polymerization solvent used in producing the (meth)acrylic polymer may be mixed as it is as a component of the adhesive coating liquid without removing it. In addition, the method for producing the adhesive coating liquid may include, but may not include, other steps other than the mixing step, and may simply mix all the components of the adhesive coating liquid by the mixing step.
[0091] Next, the adhesive coating liquid is applied to a substrate (adhesive coating liquid application step). The substrate is not particularly limited, and may be, for example, a substrate such as a film. The substrate may be, for example, a substrate made of a thermoplastic resin, a substrate made of glass, an inorganic substrate such as silicon, a plastic formed from a thermosetting resin, an element such as a semiconductor, or a carbon fiber-based material such as a carbon nanotube, but is not limited thereto. The substrate may be, for example, a film or a plate. The thermoplastic resin may be, for example, polyethylene terephthalate (PET), acrylic, cellulose acetate propionate (CAP), cycloolefin polymer (COP), triacetyl cellulose (TAC), polyethylene naphthalate (PEN), polyethylene (PE), polypropylene (PP), or the like. In the adhesive coating liquid application step, the thickness of the adhesive coating liquid is not particularly limited, and may be appropriately adjusted so that the thickness of the adhesive layer after drying is a predetermined thickness. The thickness of the adhesive layer after drying is also not particularly limited, and may be, for example, as described below.
[0092] Next, the substrate coated with the adhesive coating liquid is heated and dried (heat drying step). In this heat drying step, the temperature of the heat drying is not particularly limited, but may be, for example, 50°C or more, 80°C or more, 100°C or more, or 155°C or more, and may be, for example, 200°C or less, 180°C or less, or 160°C or less. The time of the heat drying is not particularly limited, but may be, for example, 0.5 minutes or more, 1 minute or more, or 3 minutes or more, and may be, for example, 60 minutes or less, 30 minutes or less, 20 minutes or less, or 10 minutes or less. In this heat drying step, for example, a crosslinking reaction and graft polymerization occur between the (meth)acrylic polymer and the crosslinking agent. As a result, for example, as described above, the amount of the semi-high molecular weight polymer present in the adhesive coating liquid is reduced, and the adhesive layer is less likely to penetrate into the recesses of the first optical sheet. In this manner, the adhesive layer used in the laminate of the present disclosure can be manufactured.
[0093] Next, as described above, the adhesive layer and the void layer are bonded together (bonding step). This method is not particularly limited, but for example, as described above, the adhesive layer side of an adhesive tape or the like in which the adhesive layer of the present disclosure is laminated on a substrate may be bonded onto the void layer to form the adhesive layer on the void layer. In this manner, the laminate of the present disclosure can be manufactured.
[0094] The thickness of the adhesive layer is not particularly limited, and is, for example, 0.1 to 100 μm, 5 to 50 μm, 10 to 30 μm, or 12 to 25 μm.
[0095] In the method for producing a laminate of the present disclosure, for example, a heating step of heating the adhesive layer and the void layer may be performed after the lamination step. Hereinafter, this heating step may be referred to as an "aging step". In the heating step (aging step), the heating temperature is not particularly limited, but may be, for example, 40°C or more, 45°C or more, or 50°C or more, and may be, for example, 80°C or less, 70°C or less, 60°C or less, or 55°C or less. The heating time is not particularly limited, but may be, for example, 1 minute or more, 10 minutes or more, 60 minutes or more, or 1800 minutes or more, and may be, for example, 3000 minutes or less, 2800 minutes or less, 2500 minutes or less, or 2000 minutes or less. In this aging step, for example, the intermediate layer is formed by the union of the void layer and the adhesive layer. Then, for example, the intermediate layer serves as a stopper, and the decrease in porosity caused by the voids in the void layer being filled with the adhesive can be suppressed. In addition, the integration of the void layer and the adhesive layer may be such that the adhesive layer is embedded in the voids of the void layer and chemically bonded thereto, or the adhesive layer is embedded in the voids of the void layer.
[0096] The adhesive layer can protect the void layer from physical damage (particularly scratches). The adhesive layer is preferably, but not limited to, one having excellent pressure resistance so that the void layer is not crushed even in a void layer-containing adhesive sheet that does not have a substrate (substrate-less).
[0097] The laminate of the present disclosure thus obtained may be laminated with another film (layer) to form a laminate structure including the void layer (porous structure), as described above. In this case, in the laminate structure, each component may be laminated via, for example, the adhesive layer (adhesive or adhesive).
[0098] The lamination of each of the components may be performed, for example, by continuous processing (so-called roll to roll, etc.) using a long film, since this is efficient. When the substrate is a molded product, element, etc., the components may be laminated after batch processing.
[0099] [3. Optical components] As described above, the optical member of the present disclosure includes the laminate of the present disclosure. The optical member of the present disclosure is characterized by including the laminate of the present disclosure, and other configurations are not limited at all. The optical member of the present disclosure may further include other layers in addition to the laminate, for example. The optical member of the present disclosure is, for example, in a roll shape.
[0100] [4.Optical device] As described above, the optical device of the present disclosure includes the optical member of the present disclosure. The optical device of the present disclosure is not particularly limited, and may be, for example, an image display device or a lighting device. Examples of the image display device include a liquid crystal display, an organic EL (Electro Luminescence) display, and a micro LED (Light Emitting Diode) display. Examples of the lighting device include an organic EL lighting device. EXAMPLES
[0101] Next, examples of the present disclosure will be described, but the present disclosure is not limited to the following examples.
[0102] In the following Reference Examples, Examples, and Comparative Examples, the number of parts (relative amount used) of each substance is in parts by mass (parts by weight) unless otherwise specified. In the following Reference Examples, Examples, and Comparative Examples, a pressure-sensitive adhesive (pressure-sensitive adhesive composition) described below was used as the pressure-sensitive adhesive. In the following Reference Examples, Examples, and Comparative Examples, the term "pressure-sensitive adhesive layer" corresponds to the "pressure-sensitive adhesive layer". That is, in the following Reference Examples, Examples, and Comparative Examples, the terms "pressure-sensitive adhesive layer" and "pressure-sensitive adhesive layer" are synonymous unless otherwise specified.
[0103] In addition, in the following Reference Examples, Examples, and Comparative Examples, the nanoindentation hardness, the refractive index of the void layer measured in the laminate state (Refractive Index (Laminate)), and the refractive index when only the void layer is measured (Refractive Index (Void Layer)), peel strength, and void remaining rate were each measured by the methods described in the embodiments.
[0104] In the adhesive layers in the following Reference Examples, Examples, and Comparative Examples, it is presumed that the polymer (acrylic polymer) is crosslinked by the crosslinking agent through heating and drying of the applied adhesive, thereby forming a crosslinked structure, but the crosslinked structure has not been confirmed.
[0105] [Reference Example 1: Formation of adhesive layer (adhesive 1)] The adhesive layer of this reference example (Reference Example 1) was formed by the following procedures (1) to (3).
[0106] (1) Preparation of acrylic polymer solution In a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser, 90.7 parts of butyl acrylate, 6 parts of N-acryloylmorpholine, 3 parts of acrylic acid, 0.3 parts of 2-hydroxybutyl acrylate, and 0.1 parts by weight of 2,2'-azobisisobutyronitrile as a polymerization initiator were placed together with 100 g of ethyl acetate. Next, nitrogen gas was introduced while gently stirring the contents in the four-neck flask to replace the atmosphere with nitrogen. Thereafter, the liquid temperature in the four-neck flask was kept at around 55°C and a polymerization reaction was carried out for 8 hours to prepare an acrylic polymer solution.
[0107] (2) Preparation of acrylic adhesive composition An acrylic adhesive composition (acrylic adhesive solution) was prepared by blending 0.2 parts of an isocyanate crosslinking agent (trade name "Coronate L" manufactured by Nippon Polyurethane Industry Co., Ltd., an adduct of trimethylolpropane and tolylene diisocyanate), 0.3 parts of benzoyl peroxide (trade name "Niper BMT" manufactured by Nippon Oil & Fats Corporation), and 0.1 parts of γ-glycidoxypropylmethoxysilane (trade name "KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd.) per 100 parts of the solid content of the acrylic polymer solution obtained in (1) above.
[0108] (3) Formation of adhesive layer The acrylic adhesive composition obtained in (2) above was applied to one side of a silicone-treated polyethylene terephthalate (PET) film (manufactured by Mitsubishi Chemical Polyester Film Corporation, thickness: 38 μm) so that the adhesive layer would have a thickness of 10 μm after drying, and was dried at 150° C. for 3 minutes to form adhesive layer (adhesive layer), adhesive 1.
[0109] [Reference Example 2: Formation of adhesive layer (adhesive 2)] The adhesive layer of this Reference Example (Reference Example 2) was formed by the following procedures (1) to (3).
[0110] (1) Preparation of (meth)acrylic polymer (A1) solution A monomer mixture containing 79.5 parts of butyl acrylate, 15 parts of N-acryloylmorpholine, 5 parts of acrylic acid, and 0.5 parts of 4-hydroxybutyl acrylate was charged into a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser. Furthermore, 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator was charged together with 70 parts of ethyl acetate per 100 parts of the monomer mixture, and nitrogen gas was introduced while gently stirring to replace the atmosphere with nitrogen. The liquid temperature in the flask was kept at about 55°C, and a polymerization reaction was carried out for 2 hours to prepare a solution of a (meth)acrylic polymer (A1) having a weight average molecular weight (Mw) of 3,000,000 and Mw / Mn=2.5.
[0111] (2) Preparation of (meth)acrylic adhesive composition 0.2 parts of an isocyanate crosslinking agent (trade name "Coronate L" manufactured by Nippon Polyurethane Industry Co., Ltd., an adduct of trimethylolpropane and tolylene diisocyanate) and 0.2 parts of an epoxy crosslinking agent 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane (trade name "Tetrad C" manufactured by Mitsubishi Gas Chemical Company, Inc.) were blended with 100 parts of the solid content of the obtained solution of the (meth)acrylic polymer (A1) to prepare a solution of an acrylic pressure-sensitive adhesive composition.
[0112] (3) Formation of adhesive layer Next, the solution of the acrylic adhesive composition was applied to one side of a polyethylene terephthalate film (separator film: MRF38, manufactured by Mitsubishi Chemical Polyester Film Co., Ltd.) treated with a silicone-based release agent so that the adhesive layer would have a thickness of 10 μm after drying, and was dried at 155° C. for 1 minute to form an adhesive layer (adhesive layer) of adhesive 2 on the surface of the separator film.
[0113] [Reference Example 3: Formation of adhesive layer (adhesive 3)] The adhesive layer of this reference example (Reference Example 3) was formed by the following procedures (1) to (3).
[0114] (1) Preparation of acrylic polymer solution In a four-neck flask equipped with a stirring blade, a thermometer, a nitrogen gas inlet tube, and a condenser, 99 parts of butyl acrylate, 1 part of 4-hydroxybutyl acrylate, and 0.1 parts of 2,2'-azobisisobutyronitrile as a polymerization initiator were placed together with 100 parts of ethyl acetate. Next, nitrogen gas was introduced to replace the atmosphere in the four-neck flask while gently stirring the contents. Thereafter, the liquid temperature in the four-neck flask was kept at about 55°C and a polymerization reaction was carried out for 8 hours to prepare an acrylic polymer solution.
[0115] (2) Preparation of acrylic adhesive composition A solution of an acrylic pressure-sensitive adhesive composition was prepared by blending 0.1 part of an isocyanate crosslinking agent (manufactured by Mitsui Takeda Chemical Co., Ltd. under the trade name "Takenate D110N", trimethylolpropane xylylene diisocyanate), 0.1 part of benzoyl peroxide (manufactured by Nippon Oil & Fats Co., Ltd. under the trade name "Niper BMT"), and 0.2 parts of γ-glycidoxypropyl methoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd. under the trade name "KBM-403") with 100 parts of the solid content of the acrylic polymer solution obtained in (1) above.
[0116] (3) Formation of adhesive layer The solution of the acrylic adhesive composition obtained in (2) above was applied to one side of a polyethylene terephthalate film (separator film: manufactured by Mitsubishi Chemical Polyester Film Corporation, product name "MRF38") treated with a silicone release agent, and dried at 150°C for 3 minutes to form adhesive 3, which was an adhesive layer (adhesive layer) having a thickness of 20 µm, on the surface of the separator film.
[0117] [Examples 1 to 9 and Comparative Examples 1 to 3: Production of Laminates] The laminates of Examples 1 to 9 and Comparative Examples 1 to 3 were produced by the following method.
[0118] Example 1 (1) Gelation of silicon compounds (gel silica synthesis process) Mixture A was prepared by dissolving 1.90 g of methyltrimethoxysilane (MTMS) and 0.1 g of tetraethoxysilane (TEOS), which are precursors of silicon compounds, in 4.4 g of dimethyl sulfoxide (DMSO). 1.0 g of 0.01 mol / L oxalic acid solution was added to this mixture A, and MTMS was hydrolyzed by stirring at room temperature for 30 minutes to produce a mixture B containing tris(hydroxy)methylsilane and tetra(hydroxy)silane. After adding 0.38 g of 28 wt% ammonia water and 0.2 g of pure water to 5.5 g of DMSO, the mixture B was further added and stirred at room temperature for 15 minutes to gel tris(hydroxy)methylsilane and tetra(hydroxy)silane, and a mixture C containing a gel-like silicon compound was obtained.
[0119] (2) Aging treatment The mixed solution C containing the gel-like silicon compound prepared as above was incubated as it was at 40° C. for 20 hours for aging treatment.
[0120] (3) Crushing process (gel crushing process) Next, the gel-like silicon compound aged as described above was crushed into granules of several mm to several cm in size using a spatula. Next, 40 g of isopropyl alcohol (IPA) was added to the mixed liquid C, and after light stirring, the mixture was left to stand at room temperature for 6 hours, and the solvent and catalyst in the gel were decanted. The same decantation process was performed three times to replace the solvent and obtain a mixed liquid D. Next, the gel-like silicon compound in the mixed liquid D was crushed (high-pressure media-less crushing). The crushing process (high-pressure media-less crushing) was performed using a homogenizer (manufactured by SMT Co., Ltd., product name "UH-50"), and 1.85 g of the gel-like compound and 1.15 g of IPA in the mixed liquid D were weighed into a 5 cc screw bottle, and then crushed for 2 minutes under the conditions of 50 W and 20 kHz.
[0121] By this grinding process, the gel-like silicon compound in the mixed liquid D was ground, and the mixed liquid D became a ground sol liquid E. The volume average particle diameter, which indicates the particle size variation of the ground material contained in the sol liquid E, was confirmed to be 0.50 to 0.70 μm using a dynamic light scattering nanotrack particle size analyzer (manufactured by Nikkiso Co., Ltd., UPA-EX150 type), and was found to be 0.50 to 0.70 μm. Furthermore, 0.124 g of a 1.5 wt % MEK (methyl ethyl ketone) solution of a photobase generator (Wako Pure Chemical Industries, Ltd., product name: WPBG266), which is a precursor of a crosslinking reaction accelerator, and 0.036 g of a 5% MEK solution of a crosslinking auxiliary (bis(trimethoxysilyl)hexane) were added to 0.75 g of the sol liquid E, to obtain a coating liquid 1 for forming a low refractive index layer.
[0122] The coating liquid for forming the low refractive index layer was applied to an acrylic substrate and dried to form a void layer (void ratio 59% by volume) with a film thickness of about 850 nm. The coating was performed using a wire bar, and the drying temperature and drying time were 100°C and 2 minutes, respectively. Next, UV irradiation (300 mJ) was performed from the void layer surface to bond the pulverized products of the gel-like compound together (bonding process). It is presumed that the bonding between the pulverized products of the gel-like compound in the bonding process includes at least one of crosslinking (covalent bond) in which the pulverized products are directly bonded to each other without the aid of a crosslinking auxiliary, and crosslinking (covalent bond) via the aid of the crosslinking auxiliary. Thereafter, a 10 μm thick adhesive 1 was attached to the void layer surface, and aging was performed at 50°C for 30 hours to produce the void layer of this example. The laminate of this example was also produced using the produced void layer.
[0123] Example 2 The amount of the photobase generator and the crosslinking auxiliary added in Example 1 was changed to 0.186 g of a 1.5 wt % MEK (methyl ethyl ketone) solution of the photobase generator (Wako Pure Chemical Industries, Ltd., product name: WPBG266) and 0.054 g of a 5% MEK solution of the crosslinking auxiliary (1,6-bis(trimethoxysilyl)hexane) per 0.75 g of sol solution E, but the same operation as in Example 1 was carried out to produce the void layer of this example. In addition, the laminate of this example was produced using the produced void layer.
[0124] Example 3 A laminate of this example was produced in the same manner as in Example 1, except that the amount of tetraethoxysilane (TEOS) added in Example 1 was changed to 0.2 g.
[0125] Example 4 The air gap layer of this example was manufactured by the same operation as in Example 2, except that the amount of tetraethoxysilane (TEOS) added in Example 1 was changed to 0.2 g. In addition, the laminate of this example was manufactured by using the manufactured air gap layer.
[0126] Example 5 The air gap layer of this example was produced by carrying out the same operation as in Example 1, except that the adhesive 2 was used instead of the adhesive 1 used in Example 1. In addition, the produced air gap layer was used to produce the laminate of this example.
[0127] Example 6 The air gap layer of this example was manufactured by the same procedure as in Example 1, except that the amount of tetraethoxysilane (TEOS) added in Example 1 was changed to 0.3 g. In addition, the laminate of this example was manufactured by using the manufactured air gap layer.
[0128] Example 7 The air gap layer of this example was manufactured by the same operation as in Example 1, except that the amount of tetraethoxysilane (TEOS) added in Example 1 was changed to 0.4 g. In addition, the laminate of this example was manufactured by using the manufactured air gap layer.
[0129] Example 8 The laminate of this example was produced by carrying out the same operation as in Example 1, except that 0.95 g of methyltrimethoxysilane (MTMS), which is a precursor of a silicon compound, was dissolved in 2.2 g of dimethylsulfoxide (DMSO) and tetraethoxysilane (TMOS) was not added.
[0130] Example 9 The amount of tetraethoxysilane (TEOS) added in Example 1 was changed to 0.2 g, and the amount of the photobase generator and the bis-crosslinking accelerator added was changed to 0.062 g of a 1.5 wt % MEK (methyl ethyl ketone) solution of the photobase generator (Wako Pure Chemical Industries, Ltd., product name: WPBG266) and 0.018 g of a 5% MEK solution of the bis-crosslinking accelerator ((trimethoxysilyl)hexane) per 0.75 g of sol solution E, except that the operation was performed in the same manner as in Example 1 to produce the void layer of this example. In addition, the laminate of this example was produced using the produced void layer.
[0131] Comparative Example 1 The air gap layer of this comparative example was produced in the same manner as in Example 9, except that tetraethoxysilane (TEOS) was not added. The produced air gap layer was used to produce a laminate of this comparative example.
[0132] Comparative Example 2 The air gap layer of this comparative example was produced in the same manner as in Comparative Example 1, except that the adhesive 2 was used instead of the adhesive 1 used in Comparative Example 1. The produced air gap layer was used to produce the laminate of this comparative example.
[0133] Comparative Example 3 The air gap layer of this comparative example was produced in the same manner as in Comparative Example 1, except that the adhesive 3 was used instead of the adhesive 1 used in Comparative Example 1. The produced air gap layer was used to produce the laminate of this comparative example.
[0134] [Table 1]
[0135] As shown in Table 1, the laminates of the Examples had good interlayer peel strengths of 3 N / 25 mm or more, whereas the laminates of the Comparative Examples all had interlayer peel strengths of less than 3 N / 25 mm.
[0136] FIG. 4 shows a graph showing the relationship between peel strength and refractive index of the examples and comparative examples in which the nanoindentation hardness is 0.5 MPa or more when the laminate is formed. In FIG. 4, the formula "Y=80.409x-93.718" is a linear function formula obtained by averaging two points, Comparative Example 1 and Example 8, in which no tetrafunctional silane compound was added and only the amount of the substance that generates the crosslinking auxiliary and the crosslinking reaction accelerator was changed. The formula "Y=136.4x-159.92" is a linear function formula obtained by averaging two points, Examples 1 and 2, in which 3.5 mol% of the tetrafunctional silane compound was added to the trifunctional silane compound and only the amount of the substance that generates the crosslinking auxiliary and the crosslinking reaction accelerator was changed. The formula "Y=141.37x-165.06" is a linear function formula obtained by taking the average of three points of Examples 3, 4, and 9, in which the tetrafunctional silane compound was mixed at 6.9 mol% relative to the trifunctional silane compound, and only the amounts of the crosslinking auxiliary and the substance that generates the crosslinking reaction accelerator were changed.
[0137] As shown in FIG. 4, in all the examples, the peel strength between the void layer and the adhesive layer was 3N / 25mm or more. In addition, the laminates of all the examples satisfied the condition (1) (Y≧80X-93.8) described in the embodiment. Furthermore, it was found that the laminates of the examples, which contain a tetrafunctional silane compound as a silane compound, have a higher peel strength than a void layer having the same refractive index but not containing a tetrafunctional silane compound. That is, the result satisfied the condition (2) (Y≧100X-117) described in the embodiment. In addition, by increasing the content ratio of the crosslinking auxiliary and the crosslinking reaction accelerator (the precursor of the crosslinking reaction accelerator), the peel strength was further improved.
[0138] The present disclosure can be described, for example, as in the following supplementary notes. However, the supplementary notes are merely examples, and the present disclosure is not limited to these forms.
[0139] (Appendix 1) A laminate comprising: The laminate includes a void layer and an adhesive layer, The adhesive layer is directly laminated on one or both sides of the porous layer, the refractive index of the air gap layer measured in the laminate state is 1.30 or less, The nanoindentation hardness measured by pressing an indenter into the adhesive layer by 2000 nm using a nanoindenter is 0.5 MPa or more; The peel strength between the void layer and the adhesive layer measured at a tensile speed of 0.3 m / min using a tensile tester is 3 N / 25 mm or more. Laminate. (Appendix 2) 2. The laminate according to claim 1, wherein the peel strength is 3.5 N / 25 mm or more. (Appendix 3) 3. The laminate according to claim 1 or 2, wherein the refractive index is 1.25 or less. (Appendix 4) 4. The laminate according to any one of claims 1 to 3, wherein the refractive index is X and the peel strength is Y, and the laminate satisfies the following condition (1): Condition (1): Y≧80X-93.8 (Appendix 5) 4. The laminate according to any one of claims 1 to 3, wherein the refractive index is X and the peel strength is Y, and the laminate satisfies the following condition (2): Condition (2): Y≧100X-117 (Appendix 6) 6. The laminate according to any one of claims 1 to 5, wherein the nanoindentation hardness is 1.2 MPa or less. (Appendix 7) 7. The laminate according to any one of claims 1 to 6, wherein the residual void ratio of the porous layer is 10 volume % or more after a heat and humidification durability test in which the laminate is maintained at a temperature of 85°C and a humidity of 85% RH for 500 hours. (Appendix 8) An intermediate layer is present between the void layer and the adhesive layer, 8. The laminate according to claim 1, wherein the intermediate layer is a layer formed by combining the void layer and the adhesive layer. (Appendix 9) 9. The laminate of any one of claims 1 to 8, wherein the air gap layer comprises a compound in which a silane compound is condensed or partially condensed. (Appendix 10) 10. The laminate according to claim 9, wherein the silane compound comprises a mono- to tri-functional silane compound and a tetrafunctional silane compound. (Appendix 11) The content ratio of the tetrafunctional silane compound to the amount of the monofunctional to trifunctional silane compound is 1 to 25 mol %. 11. The laminate of claim 10. (Appendix 12) The void layer is a void layer in which pulverized gel silicon compound is chemically bonded, The pulverized gel silicon compound is a compound in which the silane compound is condensed or partially condensed. 12. A laminate according to any one of claims 9 to 11. (Appendix 13) the void layer is a void layer in which the pulverized gel silicon compound is chemically bonded in the presence of an additive, The additive includes at least one of a crosslinking reaction accelerator and a precursor thereof, The precursor is a substance that generates the crosslinking reaction accelerator by the action of light or heat. 13. The laminate of claim 12. (Appendix 14) 14. The laminate according to claim 13, wherein the crosslinking reaction accelerator is an acidic substance or a basic substance. (Appendix 15) 15. The laminate according to claim 13 or 14, wherein the total content of the crosslinking reaction accelerator and its precursor is 1 mol % or more based on the total substance amount of the mono- to trifunctional silane compound and the tetrafunctional silane compound. (Appendix 16) the void layer is a void layer in which the pulverized gel silicon compound is chemically bonded in the presence of an additive, The additive includes a crosslinking auxiliary. 16. A laminate according to any one of claims 12 to 15. (Appendix 17) 17. The laminate according to claim 16, wherein the total content of the crosslinking auxiliary is 1 mol % or more based on the total substance amount of the mono- to trifunctional silane compound and the tetrafunctional silane compound. (Appendix 18) the void layer is a void layer in which pulverized gel silicon compound is chemically bonded in the presence of an additive, The gel silicon compound is a compound in which a silane compound is condensed or partially condensed, The additives include at least one of a crosslinking reaction accelerator and a precursor thereof, and a crosslinking auxiliary; Relative to the total amount of the silane compounds, The total content of the crosslinking reaction accelerator and its precursor is 1.5 mol% or more, The total content of the crosslinking auxiliary is 2.0 mol% or more. 9. A laminate according to any one of claims 1 to 8. (Appendix 19) A void layer forming step of forming the void layer; and a step of forming the adhesive layer on the void layer; Including, A method for producing a laminate according to any one of appendixes 1 to 18. (Appendix 20) The void layer forming step further includes a gel silica synthesis step, a gel crushing step, and a bonding step, The gel silica synthesis step includes a step of synthesizing a gel silicon compound by condensing or partially condensing a silane compound, The silane compound includes a monofunctional to trifunctional silane compound and a tetrafunctional silane compound, The gel crushing step includes a step of crushing the gel silicon compound to obtain a crushed product, The bonding step includes a step of chemically bonding the pulverized material. A method for producing the laminate described in Appendix 19. (Appendix 21) The void layer forming step further includes a gel silica synthesis step, a gel crushing step, and a bonding step, The gel silica synthesis step includes a step of synthesizing a gel silicon compound by condensing or partially condensing a silane compound, The gel crushing step includes a step of crushing the gel silicon compound to obtain a crushed product, The bonding step includes a step of chemically bonding the pulverized material in the presence of an additive, The additives include at least one of a crosslinking reaction accelerator and a precursor thereof, and a crosslinking auxiliary. A method for producing the laminate described in Appendix 19. (Appendix 22) An optical member comprising the laminate according to any one of claims 1 to 18. (Appendix 23) 23. An optical device comprising the optical member according to claim 22. (Appendix 24) 24. The optical device according to claim 23, which is an image display device or an illumination device. [Industrial Applicability]
[0140] As described above, according to the present disclosure, it is possible to provide a laminate, an optical member, and an optical device having a low refractive index and excellent mechanical strength. The application of the present disclosure is not particularly limited. For example, the optical device of the present disclosure is not particularly limited, and examples thereof include an image display device, a lighting device, and the like. Examples of the image display device include a liquid crystal display, an organic EL display, a micro LED display, and the like. Examples of the lighting device include an organic EL lighting device, and the like. Furthermore, the application of the laminate of the present disclosure is not limited to the optical member and optical device of the present disclosure, and is arbitrary, and can be used for a wide range of applications. [Explanation of symbols]
[0141] 10, 10a, 10b, 10c, 10d, 10e Laminate 11 Porous layer 12 Adhesive layer 13. Middle Class 14 Base material
Claims
1. A laminate comprising: The laminate includes a void layer and an adhesive layer, The adhesive layer is directly laminated on one or both sides of the porous layer, the refractive index of the air gap layer measured in the laminate state is 1.30 or less; The nanoindentation hardness measured by pressing an indenter into the adhesive layer by 2000 nm using a nanoindenter is 0.5 MPa or more; The peel strength between the void layer and the adhesive layer measured at a tensile speed of 0.3 m / min using a tensile tester is 3 N / 25 mm or more. Laminate.
2. The laminate according to claim 1 , wherein the peel strength is 3.5 N / 25 mm or more.
3. The laminate of claim 1 , wherein the refractive index is 1.25 or less.
4. 2. The laminate according to claim 1, which satisfies the following condition (1), where X is the refractive index and Y is the peel strength: Condition (1): Y≧80X-93.8
5. 2. The laminate according to claim 1, which satisfies the following condition (2), where X is the refractive index and Y is the peel strength: Condition (2): Y≧100X-117
6. The laminate according to claim 1 , wherein the nanoindentation hardness is 1.2 MPa or less.
7. 2. The laminate according to claim 1, wherein the porous layer has a residual void ratio of 10 volume % or more after a heat and humidity durability test in which the laminate is maintained at a temperature of 85° C. and a humidity of 85% RH for 500 hours.
8. An intermediate layer is present between the void layer and the adhesive layer, 2. The laminate according to claim 1, wherein the intermediate layer is a layer formed by combining the void layer and the adhesive layer.
9. The laminate according to claim 1 , wherein the gap layer comprises a compound obtained by condensing or partially condensing a silane compound.
10. The laminate according to claim 9, wherein the silane compound comprises a monofunctional to trifunctional silane compound and a tetrafunctional silane compound.
11. The content ratio of the tetrafunctional silane compound to the amount of the monofunctional to trifunctional silane compound is 1 to 25 mol %. The laminate according to claim 10.
12. The void layer is a void layer in which pulverized gel silicon compound is chemically bonded, The pulverized gel silicon compound is a compound in which the silane compound is condensed or partially condensed. The laminate according to claim 9.
13. the void layer is a void layer in which the pulverized gel silicon compound is chemically bonded in the presence of an additive, The additive includes at least one of a crosslinking reaction accelerator and a precursor thereof, The precursor is a substance that generates the crosslinking reaction accelerator by the action of light or heat. The laminate of claim 12.
14. The laminate according to claim 13, wherein the crosslinking reaction accelerator is an acidic substance or a basic substance.
15. the void layer is a void layer in which the pulverized gel silicon compound is chemically bonded in the presence of an additive, The additive includes a crosslinking auxiliary. The laminate of claim 12.
16. An optical member comprising the laminate according to claim 1 .
17. An optical device comprising the optical member according to claim 16.
Citation Information
Patent Citations
Laminate, optical member and optical device
JP2019064259A
Laminate, optical member, and optical device
JP2023051690A
Surface light-emitting device and manufacture thereof
JP1998062626A